The association of type D personality and depression with infertility in women - Esra Nur Tola; Serenat Eris Yalcin; Nadiye Dugan; Baha Oral (Taylor & Francis Group, 2020)
Purpose: Type D personality-defined as the presence of two personality characters, namely negative affectivity (NA) and social inhibition (SI)-is associated with various disorders. The 14-item Type D Scale (DS14), which consists of NA and SI subscales, can be used for the detection of the presence of Type D personality. The aim of our study was to investigate the association of Type D personality and depression with infertility in women. Method: A total of 324 women, 168 primary unexplained infertile women (92 patients undergoing in vitro fertilization (IVF) treatment and 76 undergoing intrauterine insemination (IUI) treatment) and 156 fertile controls were recruited. The 21-item Beck Depression Inventory (BDI-21) and DS14 were completed by all participants. The study was approved by Local Ethics Committee with the protocol number 72867572-050-218. Results: Depression and Type D personality were found to be significantly more prevalent in the infertile group than the fertile group. Type D was positively associated with infertility (OR = 2.34, 95% CI = 1.45-3.78, p < .0001), especially in the younger-aged (<35 years) population (OR = 2.59, 95% CI = 1.48-4.5, p = .001). After adjusting for the duration of marriage, age, obesity, educational level, and the same characteristics of the partner, the association between Type D personality and infertility persisted (OR = 2.56, 95% CI = 1.52-4.29, p < .001). The scores of the BDI-21 and NA subscale were found to be negatively correlated with age and partner's age. The BDI and SI scores, and the NA, SI, and Type D personality rates were similar between the IUI and the IVF groups; however, the NA score was higher, and depression was found to be more prevalent and severe in the IUI group than the IVF group. Conclusions: Type D personality could be positively associated with infertility, especially in younger-aged women.